Penentuan Daya Jerap Karbon Aktif Dari Pelepah Sawit Terhadap Ion Fe (III) - Muhammad Amri; Yusnimar Yusnimar; Sri Herlianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Waste pollution of heavy metals in the waters continue to rise every year. This can endanger the survival of living creatures that are in the vicinity. One contributor to the heavy metal waste in the waters is the result of discharges of industrial waste. One way to overcome the problem of heavy metal waste in the waters is the adsorption method using activated carbon as adsorbent. The purpose of this study was to determine the ability of activated carbon adsorption made from palm fronds to Fe (III). Manufacture of activated carbon from palm fronds, palm fronds initially in carbonation at a temperature of ± 280 0C to produce carbon / charcoal. Carbon generated at screening with a particle size of -100 + 200 mesh, then the activation by the chemical variation of the concentration of the activator Na2CO3 4%, 5% and 6% w/v, and carbon also in activation of physics with an activation temperature variation 300 0C, 500 0C and 700 0C. Activated carbon produced in the characterization includes: moisture content, ash content and adsorption of I2, and the data that was obtained in comparison with Standard SNI 06-3730-95. Activated carbon adsorption capability of the ion Fe (III) is determined at various concentrations 20, 40, 60, 80 and 100 mg/L. Based on the results of the characteristics of activated carbon meet ISO standards 06-3730-95, while the activated carbon adsorption capacity of the ion Fe (III) the maximum is activated carbon in the activation of physics at the activation tempetatur 700 0C, for the ion concentration of Fe (III) 80 mg/L, the activated carbon adsorption capacity is equal to 5,872 mg Fe (III)/gr activated carbon. Keywords : Activation , Activated Carbon, Ion Fe (III)